2007
DOI: 10.1111/j.1365-2958.2007.05730.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of purine nucleobase transport in Leishmania major

Abstract: SummaryLeishmania major and all other parasitic protozoa are unable to synthesize purines de novo and are therefore reliant upon uptake of preformed purines from their hosts via nucleobase and nucleoside transporters. L. major expresses two nucleobase permeases, NT3 that is a high affinity transporter for purine nucleobases and NT4 that is a low affinity transporter for adenine. nt3 (-/-) null mutant promastigotes were unable to replicate in medium containing 10 mM hypoxanthine, guanine, or xanthine and replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 44 publications
(49 reference statements)
1
54
0
1
Order By: Relevance
“…Generation of the ⌬lmant-null mutant and complementation with the LmaNT3 and LmaNT4 genes have been described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of the ⌬lmant-null mutant and complementation with the LmaNT3 and LmaNT4 genes have been described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…Salvage of these essential nutrients is initiated by uptake of nucleobases and nucleosides across the parasite plasma membrane by permeases of the ENT (equilibrative nucleoside transporter) family (SLC29 family). The Leishmania major genome (3) encodes five members of this family, NT1.1, NT1.2, and NT2, which are nucleoside transporters (4,5), and NT3 and NT4, which are purine nucleobase permeases (6,7). Previous functional characterization of LmaNT3 (Lma indicates that the transporter is from L. major) revealed that it mediates the uptake of hypoxanthine, adenine, guanine, and xanthine with K m values in the low micromolar range (6).…”
mentioning
confidence: 99%
“…However, while a double null mutant of the nucleoside transporters (⌬nt1 ⌬nt2) was viable (58), it was impossible to generate a dual null mutant (⌬nt3 ⌬nt4) of the nucleobase transporters (74). This result implies that purine nucleobases play a particularly important role in purine salvage.…”
Section: Purine Transportersmentioning
confidence: 82%
“…Gene knockout studies have revealed that none of these 4 purine permeases is essential for viability of either promastigotes (insect stage) or amastigotes (intramacrophage vertebrate stage) (58,74). However, while a double null mutant of the nucleoside transporters (⌬nt1 ⌬nt2) was viable (58), it was impossible to generate a dual null mutant (⌬nt3 ⌬nt4) of the nucleobase transporters (74).…”
Section: Purine Transportersmentioning
confidence: 99%
See 1 more Smart Citation